Evaluating the Guiding Role of Elevated Pretreatment Serum Carcinoembryonic Antigen Levels for Adjuvant Chemotherapy in Stage IIA Colon Cancer: A Large Population-Based and Propensity Score-Matched Study - Liu, Qi; Huang, Yongqiang; Luo, Dakui; Zhang, Sheng; Cai, Sanjun; Li, Qingguo; Ma, Yanlei; Li, Xinxiang (Frontiers in Oncology, 2019)
Objective: This study was to investigate guiding role of elevated pretreatment serum carcinoembryonic antigen (CEA) levels for ACT receipt in stage IIA colon cancer. Methods: Eligible patients diagnosed with stage IIA colon cancer (N = 21848) were identified from the Surveillance, Epidemiology, and End Results (SEER) database between January 2004 and December 2010. Pearson's chi-squared tests, Cox proportional hazards regression models, and Kaplan-Meier methods were performed. Propensity score matching (PSM) was used to decrease the risk of biased estimates of treatment effect. Results: Multivariate Cox analysis indicated that, in CEA-elevated group, receiving or not receiving ACT did not presented statistically CSS difference [hazard ratio (HR) = 0.940, 95% confidence interval (CI) = 0.804–1.097, P = 0.431]; in CEA-normal group, receiving or not receiving ACT also did not presented statistically CSS difference (HR = 0.911, 95% CI = 0.779–1.064, P = 0.239). After PSM, Kaplan-Meier analyses showed that there was no statistical CSS difference between receiving or not receiving ACT (P = 0.64). Conclusion: ACT did not show substantial survival benefit in stage IIA colon cancer with elevated pretreatment serum CEA levels. Stage IIA disease with elevated pretreatment serum CEA should not be treated with ACT.